Kacaping: traditional picked music product inspiration of the Bugis Sailing community in South Sulawesi - Ihsan, Andi; Hasbi, Hasbi (International Journal of Visual and Performing Arts, 2024)
Kacaping is a traditional musical instrument that holds significant cultural relevance in South Sulawesi, particularly among Bugis tribe. Its boat-like shape links its origins to skilled sailors who created it long ago. Kacaping continues to play a vital role in community events such as weddings, aqiqah, and government gatherings. In the educational context, kacaping is incorporated into local content curricula, showcasing traditional performances. Recently, the evolution of kacaping into a diatonic version known as kitoka has emerged. However, many young individuals recognize kacaping merely as an art form, often unaware of its historical significance and cultural lineage. This research aims to elucidate the role of kacaping as a traditional music product reflecting the maritime heritage of the Bugis community. Employing a descriptive qualitative approach, data were collected through observations, interviews, and documentation, subsequently analyzed and verified. Participants in this study included cultural figures, instrument makers, performers, and educators. The findings confirm that kacaping is deeply rooted in the seafaring culture of the Bugis, with its historical and functional evolution evident in written documents and the presence of similar boat-like instruments in households. This research underscores the importance of fostering an appreciation for kacaping among the youth, highlighting its ancestral values beyond mere artistic expression, and encouraging academic and cultural literacy in schools.